Australian impact cratering record: Updates and recent discoveries - Quintero, Raiza R.; Cavosie, Aaron; Cox, Morgan A.; Miljković, Katarina; Dugdale, Allison (2021)
There are currently 31 confirmed structures of impact origin in Australia. More than 49 additional structures have been proposed to have formed due to asteroid impact but await confirmation. Many discoveries have been made in Australia in the time since the last comprehensive review of the Australian impact cratering record was published in a peer-reviewed journal in 2005. These include further expanding the record of confirmed craters, and providing new insights into a variety of impact-related processes, such as shock deformation, phase transitions in accessory minerals, new impact age determinations, studies of oblique impacts, and more. This update is a review that focuses principally on summarizing discoveries made since 2005. Highlights since then include confirmation of five new Australian impact structures, identification of Earth's oldest recognized impact structure, recognition of shock deformation in accessory minerals, discovery of the high-pressure phase reidite in Australia, determination of the links between impact craters and some ore deposits, and publication of the first generation of numerical hydrocode models for some Australian craters.